Black out: a novel (Thorndike Press large print thriller, ,, 2009)
A woman has to quickly piece together disturbing events--one of which is the murder of her psychologist--before her past comes to claim her future and her daughter.

A cure for night (Thorndike Press large print thriller, ,, 2009)
Yale Law School graduate Justin Peacock's legal experience serves him well for this intense novel in the tradition of such genre luminaries as Scott Turow and Richard Price. A Cure for Night features Joel Deveraux, a former corporate-law hotshot whose downward slide finds him plying his trade at Brooklyn's Public Defender's office. Thrust into a high-profile case involving black-on-white crime, Joel quickly discovers he is in over his head.

Envy the night (Thorndike Press large print thriller, ,, 2008)
"It has been seven years since Frank Temple III joined the rest of the world in learning his father's bloody secret: The U.S. marshal maintained a covert career as a contract killer, a double-life that ended in suicide to avoid prosecution and prison. The shocking revelation triggered years of anonymous drifting for Frank, time spent running from his legacy and struggling to believe that the father he'd loved so dearly was entirely in the wrong. After all, the victims hadn't been innocents. And Devin Matteson, the man who'd lured his father into the killing game only to later give him up to the FBI, is probably the darkest of the lot. Those are troubling thoughts, and Frank tries to stay away from them. But when an old family friend calls to say that Matteson is returning to the isolated Wisconsin lake that was once sacred ground for their families, it's a homecoming Frank knows he can't allow. His arrival in town reveals a situation far from the expected, though. While Matteson is nowhere to be found, his old cabin is indeed occupied - by a strange, beautiful woman and a nervous man with a gun. When a pair of assassins from Miami arrive on their heels, Frank knows Matteson can't be far behind. And while the wise move would be to call in the police and get out of town fast, that just doesn't feel right. After all, contract killer or not, Frank's father was at heart a teacher. And his son excelled at the lessons."--BOOK JACKET.

The last embrace (Thorndike Press large print thriller, ,, 2008)
Los Angeles 1949. A city of big dreams and dark shadows... Lily Kessler, a former stenographer and spy for the OSS, comes to Los Angeles to find her late fiancé's sister Kitty, an actress who is missing from her Hollywood boardinghouse. The next day, Kitty's body is found in a ravine below the Hollywood sign. Unimpressed by the local police, Lily investigates on her own. As she delves into Kitty's life, she encounters fiercely competitive starlets, gangsters, an eccentric special-effects genius, exotic denizens of Hollywood's nightclubs, and a homicide detective who might distract her from her quest for justice. But the landscape in L.A. can shift kaleidoscopically, and Lily begins to see how easily a young woman can lose her balance and fall prey to the alluring city's dangers.... With vibrant characters and unerring insight into the desires and dark impulses that can flare between men and women, The Last Embrace showcases Denise Hamilton at the height of her storytelling powers as she transports readers to a fascinating, transitional time in one of America's most beguiling cities.

The other side of silence: a novel of suspense (Thorndike Press large print thriller, ,, 2008)
On his third day in Death Valley, Rick Fallon comes upon a deserted Toyota Camry, and soon thereafter, the almost-dead body of Casey Dunbar. Having rescued her, Fallon soon learns what had driven her to give up on life--and, his own life on hold, he resolves to unravel the twisted and dangerous strands of hers, a quest that leads him to the glitter-dome of Las Vegas.

The Seven Sins: the tyrant ascending (Michael Tirrano novels, 1, 1, 2008)
To Dream...To Dare..To Win... The ancient motto, inscribed in Latin on a mysterious golden medallion, recovered from the ruins of the Roman Empire, has guided Michael Tiranno to heights few men have achieved. Once an orphaned farm boy in his native Sicily, Michael made millions by mastering the intricate world of high finance, and is now the fabulously wealthy owner of Las Vegas' The Seven Sins, the grandest and most extravagant casino in the world. The lavish resort embodies the personal philosophy fueled by his lust for power: the greater the risk, the greater the reward. But he also has secrets, secrets that he and Naomi Burns, his driven corporate attorney and confidante, have gone to great lengths to bury. When an enemy from the past threatens to undermine everything he has built, his dark history must now be uncovered. Together, they must tear open painful scars in Michael's heart and soul to discover the true identity of their unknown foe-before all of Las Vegas pays the price for Michael Tiranno's realized dreams. The Seven Sins is a globe-spanning saga of one man's spectacular rise from rags to riches, the sins that brought him there, and the insidious vendetta that may cost him everything. At the Publisher's request, this title is being sold without Digital Rights Management Software (DRM) applied.

Tailspin (FBI suspense thriller series, 12, 1, 2009)
FBI Special Agents Dillon Savich and Lacey Sherlock are assigned to protect Dr. MacLean, a physician with frontal lobe dementia that could compromise his ability to maintain doctor-patient confidentiality. With a patient list made up of Washington movers and shakers, MacLean's role as a keeper of secrets is jeopardized as well. Is there someone out there so desperate that they'd kill the doctor for what he knows? It is up to Jackson, Savich, and Sherlock to find out--no matter the cost.

The 13th hour: a thriller (Thorndike Press large print thriller, ,, 2009)
Accused of murdering his wife Mary, Nick Quinn travels back in time to find clues to the identity of her real killer and perhaps save Mary's life. But all his good intentions may in fact lead to a far greater catastrophe than he could have imagined.

No survivors: an accident man novel (Samuel Carver novels, 2, 1, 2009)
Description Not Provided

Risk (Thorndike Press large print thriller, ,, 2009)
An honest lawyer, a Czech hand model, and a box of mysterious Christmas ornaments--each plays a part in Colin Harrison's compelling new intrigue George Young never thought of himself as a detective, but that's pretty much his vocation--an attorney at a top insurance firm, it's his job to pin down suspicious claims. But Mrs. Corbett, the rich, eccentric wife of the firm's founder, has it in mind to put George's skills to a peculiar assignment. With only a few months left to live, her one desire is to know the true circumstance of her son Roger's violent death. George's investigation leads him to Roger's mistress, a cagey Czech hand model named Eliska, who can cast a seductive spell simply by removing her gloves. Did Eliska's motives for latching on to Roger get him killed? Or did some of her shadowy and dangerous little friends take care of the job? And why were there boxes and boxes of Christmas ornaments in the dead man's apartment? George will have to take a few chances of his own if he wants to get to the bottom of Roger's death for Mrs. Corbett. Set against a volatile and vividly drawn Manhattan, Risk is prime Colin Harrison.

Wrongful death (David Sloane thrillers, 2, 1, 2009)
Just minutes after winning a $1.6 million wrongful-death verdict, attorney David Sloane confronts the one case that threatens to blemish his unbeaten record in the courtroom. Beverly Ford wants Sloane to sue the United States goverment and military in the mysterious death of her husband, James, a national guardsman killed in Iraq. While a decades-old military doctrine might make Ford's case impossible to win, Sloane, a former soldier himself, is compelled to find justice for the widow and her four children in what is certain to become the biggest challenge of his career.

Capitol betrayal (Ben Kincaid novels, 18, 1, 2010)
When a malevolent foreign dictator hacks into the U.S. nuclear defense system, the president comes under fire. With the clock winding down, lawyer Ben Kincaid has precious little time to defend the president. While Kincaid faces the trial of his life, legendary CIA agent Seamus McKay races through the clogged streets of Washington, searching for a hidden command center--guarded by murderous fanatics--that now controls U.S. ballistic missiles.

Death on the D-list (Hailey Dean thrillers, 2, 1, 2010)
After she moves to New York City and becomes a TV crime fighter, former felony prosecutor Hailey Dean learns that the television industry is filled with treachery. A killer is targeting a series of beautiful actresses, each one a former star struggling to get back into the limelight.

Eight days to live (Eve Duncan novels, 10, 1, 2010)
Eve Duncan's adopted daughter Jane has been targeted by a mysterious cult who has decided that she has only eight days to live.

The liar's lullaby (Jo Beckett series, 3, 1, 2010)
When the country singer ex-wife of a U.S. president is sensationally murdered during a concert performance, forensic psychiatrist Jo Beckett endeavors to learn the victim's role in her demise as well as the murder's relevance for the president.

Zero history (Blue Ant trilogy, 3, 1, 2011)
Hollis Henry worked for the global marketing magnate Hubertus Bigend once before. She never meant to repeat the experience. But she's broke, and Bigend never feels it's beneath him to use whatever power comes his way - in this case, the power of money to bring Hollis onto his team again. Not that she knows what the "team" is up to, not at first. Milgrim is even more thoroughly owned by Bigend. He's worth owning for his useful gift of seeming to disappear in almost any setting, and his Russian is perfectly idiomatic, so much so that he spoke Russian with his therapist, in the secret Swiss clinic where Bigend paid for him to be cured of the addiction that would have killed him.

The betrayal (Precinct 11, 2, 1, 2011)
Detective Boone Drake has just masterminded the most massive sting in Chicago history, bringing down the heads of not only the biggest street gangs in the city, but also the old crime syndicate. The story is the biggest in decades, and the Chicago PD must protect the key witness at all costs. Despite top secret plans to transfer the witness to testify before the grand jury, an attempt is made on his life. And the source of the leak may be one of their own.

Bonnie (Eve Duncan novels, 14, 1, 2012)
"When Eve Duncan gave birth to her daughter, she experienced a love she never knew existed. Nothing would stand in the way of giving Bonnie a wonderful life, until the unthinkable happened and the seven-year-old vanished into thin air. Eve found herself in the throes of a nightmare from which there was no escape. But a new Eve emerged: a woman who would use her remarkable talent as a forensic sculptor to help others find closure in the face of tragedy. Now, with the help of her beloved Joe Quinn and CIA Agent Catherine Ling, Eve has come closer than ever to the truth. But the deeper she digs, the more she realizes that Bonnie's father is a key player in solving this monstrous puzzle. And that Bonnie's disappearance was not as random as everyone had always believed"--From publisher description.

Gideon's war (Gideon Davis thrillers, 1, 1, 2011)
Exposed to covert information by his work as an international negotiator, Gideon Davis is tapped by a government bigwig to chaperone a rogue agent, Gideon's brother, whose surrender is foiled by a terrorist plot involving a multi-million-dollar oil rig.

The informationist: a thriller (Vanessa Michael Munroe novels, 1, 1, 2011)
Vanessa "Michael" Munroe deals in information-expensive information-working for corporations, heads of state, private clients, and anyone else who can pay for her unique brand of expertise. Born to missionary parents in lawless central Africa, Munroe took up with an infamous gunrunner and his mercenary crew when she was just fourteen. As his protégé, she earned the respect of the jungle's most dangerous men, cultivating her own reputation for years until something sent her running. After almost a decade building a new life and lucrative career from her home base in Dallas, she's never looked back.Until now.A Texas oil billionaire has hired her to find his daughter who vanished in Africa four years ago. It's not her usual line of work, but she can't resist the challenge. Pulled deep into the mystery of the missing girl, Munroe finds herself back in the lands of her childhood, betrayed, cut off from civilization, and left for dead. If she has any hope of escaping the jungle and the demons that drive her, she must come face-to-face with the past that she's tried for so long to forget.